ANALISIS KEMAMPUAN FOOTWORK KUMITE - Destsari, Veggi; Samodra, Y. Touvan Juni; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problems in this research there were no data on the effectiveness of what kumite footwork were often done and how efficient the kumite footwork technique has scored points. The purpose of this study were to find out how effective kumite footwork and what kind of kumite footwork techniques most efficient in getting points. The research method were descriptive done by analyzing the ability of kumite footwork. The research subjects were karate athletes of the -50kg women's grade kumite match at the sports week of the province of West Kalimantan, amount of to 6 people. The data of this study were obtained from the video of the match. The results prove that the zenkutsudachi kumite footwork is the most effective and the kumite footwork with the Kizame Chuki technique is performed most often as much as 44% of all matches. The data of all research matches are kumite footwork with gyaku chuki technique 36%, kumite footwork with maegeri 3% technique, kizame ushiro geri 8%, gyaku mawashi gery 0%, mawashi geri 0%, counter 5%, mayashi geri 2% and combination 2 geri %. Keywords: Footwork, Kumite